Cosmic Ray Detection with RNO-G - Nelles, Anna (Proceedings of Science, 2024)
The Radio Neutrino Observatory-Greenland (RNO-G) is an in-ice neutrino detector aiming for the first detection of neutrinos at energies exceeding 10 PeV. Positioned on top of the Greenland ice sheet close to Summit Station, the detector is presently in the construction phase, with 7 out of 35 planned stations already deployed within the ice and operational. Each station is not only equipped with antennas designed to detect neutrino signals but also features three upward-facing log-periodic dipole array antennas (LPDA). These antennas are included to detect signals from cosmic-ray air-showers. Upon completion, the detector will cover an area of O(50)km2, allowing RNO-G to measure cosmic-ray air-showers and use them for detector calibration, study the phenomenon of the air-shower core hitting the ice, and veto cosmic-ray events for the neutrino search.
CRIS-Team Scopus Importer:2025-02-04